Qualification problems of war-related criminal offences documented on the de-occupied territories of Ukraine (Law and Safety, 2022)
The article is devoted to the characteristics of the main qualification problems of criminal offenses related to the war in the context of the de-occupation movement. Based on the analysis and synthesis of the experience of investigators from the National Police, the Security Service of Ukraine, as well as prosecutors on the de-occupied territories of Ukraine, four basic problematic subject areas with the corresponding typical situations of the law on criminal liability application have been identified: criminal legal qualification of artillery shelling, mining, causing death to a person, and other actions of physically detained representatives of the aggressor state. For each zone and situation, the main approaches to the qualification of documented criminal offenses and other events used in law enforcement practice have been identified. A critical analysis of these approaches has been carried out, shortcomings are identified, and ways to eliminate them are proposed.